Oyu Tolgoi ore handling system truck chute development, raisebore and construction evolution - Taisuren, M; Enkhbayar, O; Dolgorjav, B; Davaajav, K; Stobbart, P; Whyatt, CS (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
This paper outlines the development of truck chutes at Oyu Tolgoi Underground (OTUG), which are a key infrastructure component of the material handling system, along with an outline of method improvements associated with their construction. OTUG HNL1 Panel 0 was successfully established without any delays to the ore handling system. Completion of a truck chute requires several major construction stages: mass excavation chamber development, raiseboring, shotcrete lining and steel can lining, extraction level (EXL) tipple construction, and haulage level (HLL) chute construction. During the initial construction of the early truck chutes, significant challenges were encountered, particularly during raiseboring through geotechnically weak and faulted ground. These issues included raise collapse and difficulties installing the steel can due to ground movement. The construction duration of each truck chute, which was therefore extensive. Several method improvements were implemented across all stages throughout the development and construction of the Panel 0 truck chutes. Haulage Level chute mass excavation chamber development sequencing was optimised to better align with the overall construction sequence. Raiseboring adopted chokereaming and shrinklining methods to minimise the risk of raise collapse in weak ground conditions. Truck chute construction design and constructability were improved, and the capability of the national construction team competency was significantly enhanced, resulting in a notable reduction in construction duration. Collectively, these improvements significantly shortened the overall truck chute completion timeline. This progress provides strong confidence in the team’s ability to deliver the remaining truck chutes across multiple panels on schedule, while avoiding with unplanned schedule impacts due to poor ground conditions.
Keywords: raisebore; poor ground conditions; truck chute construction